Perancangan Sistem Informasi Posyandu Berbasis Web Pada Yayasan Kalyanamitra Di Jakarta Timur Untuk Mendukung Program Bidang Pendampingan Komunitas - Angelina Ervina Jeanette Egeten; Siska A. Damanik; Ika Agustina; Marcelina Panggabean (Universitas Bumigora, 2019)
The objective of this research is to design an Information system of Pos Pelayanan Terpadu (Posyandu), especially to toddlers, pregnant women, and the elderly to support the performance of the Community Asisstance in Kalyanamitra Foundation. The analysis using System Development Life Cycle (SDLC) method with waterfall model and the design using the Object-Oriented Analysis and Design (OOAD) method with defining all objects interaction which are described by the UML (Unified Modeling Language) diagram. The analysis was applied on current working system and the result became the basis for designing a Posyandu web-based information system to assist the implementation of Posyandu for toddlers, pregnant women, and the elderly, especially in registering, documenting and storing data, and reporting which correspond to organizational needs. Posyandu information system supports Kalyanamitra Foundation's program in intervening with local government to improve the quality of Posyandu services and facilities.